159k views
4 votes
How do you do this problem?

How do you do this problem?-example-1

2 Answers

2 votes

You can let q = (x-4)². Then you have

... f(q) = q - 1

... g(q) = -q/4 + 4

Putting these into the equation f - g = 0 gives you

...q - 1 - (-q/4 + 4) = 0

... (5/4)q = 5 . . . . collect terms, add 5

... q = (4/5)·5 = 4 . . . . multiply by the inverse of the q coefficient

Relating this back to x, you have

... (x -4)² = 4

... x - 4 = ±2 . . . . take the square root

... x = 4 ± 2 = {2, 6} . . . . . . add 4 to find x (there are two solutions)

The appropriate choice is

... (C) 6

User Mayeru
by
5.3k points
6 votes

f(x) = (x - 4)^2 - 1

g(x) = -(1/4) ( x - 4)^2 + 4

both the x and y values have to be the same. Start with the y values

f(x) = g(x)

(x - 4)^2 - 1 = -(1/4) (x - 4)^2 + 4 Add 1 to both sides.

(x - 4)^2 = -(1/4) (x - 4)^2 + 5 Add 1/4(x - 4)^2 to both sides.

(5/4) (x - 4)^2 = 5 Divide by 5/4 on both sides.

(x - 4)^2 = 5//(5/4)

(x - 4)^2 = (5/1)//5/4 Invert the second fraction and multiply

(x - 4)^2 = 5/1 * 4/5

(x - 4)^2 = 4 The 5s cancel

(x - 4)^2 = 4 Take the square root of both sides.

(x - 4) = +/- 2 Add 4 to each answer. Start with +2 on the right.

x - 4 + 4 = 2 + 4

x = 4 + 2 = 6

The x value that makes f(x)- g(x) = 0 is x = 6 The point is (6,3) answer.

Answer C.

================================================

You do not need this next part. It is just for completeness.

x - 4 = - 2

x = 4 -2

x = 2

What are the y values for these 2 x values?

y = (x - 4)^2 - 1

y = (6 - 4)^2 - 1

y = 4 - 1

y = 3

The point where f(x) - g(x) = 0 is (6,3) <<<<<< Answer 1

The second point is

y = (x - 4)^2 - 1

y = (2 - 4)^2 - 1

y = (-2)^2 - 1

y = 4 - 1

y = 3

The second point is (2,3). Answer 2

Note the y values are the same. You might expect that.

User Tim Gradwell
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.